PENGARUH MEDIA AUDIO VISUAL,VIDEO TERHADAP PENGUASAAN GERAK DASAR “TENDANGAN” PENCAK SILAT PADA ANGGOTA PERGURUAN CIMANDE DESA SUKADAMAI KECAMATAN TANJUNG LAGO KABUPATEN BANYUASIN - Ali Nurdin; Perabunita Perabunita; Ahmad Muchlisin Natas Pasaribu (Universitas Singaperbangsa Karawang, 2020)
This study aims to describe the presence of the influence audiovisual media on mastery of the basic movements of pencak silat kicks at the Cimande college, Sukadamai village, Tanjung Lago Regency Banyuasin. The research method in the research to be carried out is a pretest-posttest design one-group experiment. The samples in this study were 25 Cimande martial arts college members. The instruments used in this study were the pretest and posttest tests. Data analysis was performed that is normality test, homogeneity test and hypothesis test. Based on the results of t straight test t count value of 8.515 while the value of ttable = 1.71, then tcount> t table with a significant value of 0.000. On the crescent kick the value of tcount = 9,474 while the value of t table = 1.71, then tcount> t table with a significant value of 0.000. In the side kick get the value of tcount = 5,846 while the value of ttable = 1.71, then tcount> ttable with a significant value of 0.000. After analyzing the three data, tcount>ttable is obtained. In accordance with the hypothesis testing criteria used if tcount> ttable, Ho which states there is no influence of the use of audiovisual video media on the basic movements of pencak silat in Cimande college, Sukadamai village, Tanjung Lago subdistrict, Banyuasin district. rejected. So Ha who stated that there was an influence of the use of audiovisual video media on the basic movements of Cimande martial arts in Sukadamai village, Tanjung Lago district, Banyuasin district was accepted.